Application of composite film with multi-element and multi-phase structure in surface lubrication of aerospace vehicle or nuclear power bearing in high-temperature environment

By applying composite films with a diverse and multi-phase structure on the surfaces of aerospace vehicles and nuclear power bearings, the problem of insufficient oxidation and hardness of MoS2 films in high temperature environments is solved, and stable lubrication and long life and reliable service in harsh environments are achieved.

CN119710589APending Publication Date: 2025-03-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411900696.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing MoS2 films are prone to oxidation in high temperature environments, resulting in degradation of lubrication performance and insufficient hardness under high-speed heavy load conditions, resulting in early failure, making it difficult to meet the stable lubrication needs of aerospace vehicles and nuclear power bearings in harsh environments.

Method used

A composite film with a multi-phase structure is adopted, including a titanium transition layer, a titanium/molybdenum disulfide/tantalum/tungsten diboride gradient transition layer, and a molybdenum disulfide/tantalum/tungsten diboride composite layer. The latter consists of tantalum nanoparticles, a molybdenum disulfide layer and a tungsten diboride layer. The tantalum nanoparticles are distributed between the molybdenum disulfide layer and the tungsten diboride layer.

Benefits of technology

Improve the hardness, elastic modulus and hard/elastic ratio of the film at atmospheric room temperature, and maintain high hardness and low friction coefficient at high temperature of 400°C, extending the service life of aerospace vehicles and nuclear power bearings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710589A_ABST
    Figure CN119710589A_ABST
Patent Text Reader

Abstract

The invention discloses application of a composite film with a multi-element and multi-phase structure in surface lubrication of an aerospace vehicle or a nuclear power bearing in a high-temperature environment. The composite film comprises a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-element and multi-phase structure layer which are sequentially formed on the surface of a base body. The multicomponent multiphase structure layer comprises a molybdenum disulfide / tantalum / tungsten diboride composite layer, the molybdenum disulfide / tantalum / tungsten diboride composite layer comprises tantalum nanoparticles, a molybdenum disulfide layer and a tungsten diboride layer, and the tantalum nanoparticles are distributed between the molybdenum disulfide layer and the tungsten diboride layer. The composite film with the multi-element and multi-phase structure shows higher hardness and hardness / elasticity ratio and low friction coefficient and wear rate at the high temperature of 400 DEG C, and meanwhile, the composite film can meet stable lubrication and long-life reliable service of aerospace vehicles and nuclear power bearings under harsh and complex variable working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface protection treatment, and specifically relates to the use of a composite film with a multi-component multi-phase structure in the lubrication of aerospace vehicle or nuclear power bearing surface under a high temperature environment. Background Art

[0002] Molybdenum disulfide (MoS2), as a typical transition metal disulfide (TMD), has excellent solid lubrication properties due to its unique layered structure and weak van der Waals interaction between layers. These properties make MoS2 an indispensable material in the fields of aerospace, nuclear energy, and high-precision mechanical electronics, especially in applications under extreme environments. MoS2 film can effectively prevent cold welding and high friction of mechanical equipment in vacuum or thin atmosphere. However, MoS2 is extremely sensitive to environmental conditions, especially its performance in high temperature environments. Under high temperature conditions, MoS2 film is prone to oxidation reaction, and its chemical structure is destroyed, resulting in a significant decrease in lubrication performance, thereby affecting the overall mechanical stability and service life. In addition, under high-speed and heavy-load application conditions, the inherent hardness of MoS2 film is insufficient, which may lead to film peeling or early failure, especially in the process of launch and on-orbit operation of spacecraft and satellites, which often face high and low temperature alternation, high humidity and heat, and other complex physical and chemical conditions. These factors have put forward higher requirements on the reliability and stability of MoS2 film. The existing MoS2 film modification technology and multilayer system can no longer meet the service damage conditions faced by aerospace mechanical motion devices in harsh environments. Summary of the invention

[0003] The main purpose of the present invention is to provide a composite film with a multi-component multi-phase structure for use in the lubrication of aerospace or nuclear power bearing surfaces under high temperature environments, so as to overcome the shortcomings of the prior art.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0005] An embodiment of the present invention provides a composite film with a multi-component multi-phase structure for use in the lubrication of aerospace or nuclear power bearing surfaces under high temperature environments, wherein the composite film comprises a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-component multi-phase structure layer sequentially formed on the surface of a substrate; wherein the multi-component multi-phase structure layer comprises a molybdenum disulfide / tantalum / tungsten diboride composite layer, the molybdenum disulfide / tantalum / tungsten diboride composite layer comprises tantalum nanoparticles, a molybdenum disulfide layer and a tungsten diboride layer, and the tantalum nanoparticles are distributed between the molybdenum disulfide layer and the tungsten diboride layer.

[0006] Compared with the prior art, the present invention has the following beneficial effects:

[0007] (1) The composite film with a multi-element multi-phase structure in the present invention has high hardness, elastic modulus and hardness / elasticity ratio at room temperature; the design of the composite film can effectively improve the hardness, elastic modulus and load-bearing capacity of the film, and the incorporation of tantalum nanoparticles can repair interface defects and improve the bonding strength between the molybdenum disulfide layer and the tungsten diboride layer;

[0008] (2) The composite film with a multi-component multi-phase structure in the present invention exhibits higher hardness and hardness / elasticity ratio and lower friction coefficient and wear rate at a high temperature of 400°C. The composite film can meet the requirements of stable lubrication and long-life reliable service of aerospace and nuclear power bearings under harsh and complex variable working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0010] Figure 1 The XRD diagrams of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 are shown;

[0011] Figure 2 is a cross-sectional TEM image of the composite film obtained in Example 1 of the present invention;

[0012] Figure 3 is a TEM high-resolution image of the composite film prepared in Example 1 of the present invention;

[0013] Figure 4a is a cross-sectional SEM image of the composite film prepared in Example 1 of the present invention;

[0014] Figure 4b is a cross-sectional SEM image of a pure molybdenum disulfide film obtained in Comparative Example 1 of the present invention;

[0015] Figure 4c is a cross-sectional SEM image of the molybdenum disulfide / tungsten diboride film prepared in Comparative Example 2 of the present invention;

[0016] Figure 5a is a surface SEM image of the composite film prepared in Example 1 of the present invention;

[0017] Figure 5b is a surface SEM image of the pure molybdenum disulfide film prepared in Comparative Example 1 of the present invention;

[0018] Figure 5cis a surface SEM image of the molybdenum disulfide / tungsten diboride film prepared in Comparative Example 2 of the present invention;

[0019] Figure 6a is a SPM image of the composite film prepared in Example 1 of the present invention;

[0020] Figure 6b is a SPM image of a pure molybdenum disulfide film obtained in Comparative Example 1 of the present invention;

[0021] Figure 6c is a surface SPM image of the molybdenum disulfide / tungsten diboride film prepared in Comparative Example 2 of the present invention;

[0022] Figure 7a is a graph of hardness and elastic modulus of the composite film prepared in Example 1 of the present invention at room temperature and high temperature;

[0023] Figure 7b Graph showing the hardness and elastic modulus of the pure molybdenum disulfide film obtained in Comparative Example 1 of the present invention at room temperature and high temperature;

[0024] Figure 7c Graph showing the hardness and elastic modulus of the molybdenum disulfide / tungsten diboride film obtained in Comparative Example 2 of the present invention at room temperature and high temperature;

[0025] Figure 8 It is a hardness / elasticity ratio diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 under atmospheric room temperature and high temperature environments;

[0026] Figure 9a is a cross-sectional SEM image of the composite film prepared in Example 1 of the present invention before a 400° C. high-temperature nanoindentation test;

[0027] Figure 9b is a cross-sectional SEM image of the composite film prepared in Example 1 of the present invention after a high-temperature nanoindentation test at 400°C;

[0028] Fig.10a It is a friction coefficient curve diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 at 25°C;

[0029] Fig.10b It is a friction coefficient curve diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 at 100°C;

[0030] Fig.10cIt is a friction coefficient curve diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 at 200°C;

[0031] Fig.10d It is a friction coefficient curve diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 at 300°C;

[0032] Fig.10e is a friction coefficient curve of the composite film prepared in Example 1 of the present invention and the molybdenum disulfide / tungsten diboride film prepared in Comparative Example 2 at 400° C.;

[0033] Fig.11 It is a graph of average friction coefficient of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Comparative Examples 1 and 2 at room temperature and high temperature (25-400° C.);

[0034] Fig.12 It is a wear rate diagram of the composite film prepared in Example 1 of the present invention and the pure molybdenum disulfide and molybdenum disulfide / tungsten diboride films prepared in Control Examples 1 and 2 at room temperature and high temperature environment (25-400°C). DETAILED DESCRIPTION

[0035] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Specifically, as one aspect of the technical solution of the present invention, it involves the use of a composite film with a multi-phase structure in the surface lubrication of aerospace vehicles or nuclear power bearings under high temperature environment, the composite film includes a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-phase structure layer formed in sequence on the surface of a substrate; wherein the multi-phase structure layer includes a molybdenum disulfide / tantalum / tungsten diboride composite layer, the molybdenum disulfide / tantalum / tungsten diboride composite layer includes tantalum nanoparticles, a molybdenum disulfide layer and a tungsten diboride layer, and the tantalum nanoparticles are distributed between the molybdenum disulfide layer and the tungsten diboride layer.

[0037] In some preferred embodiments, the temperature of the high temperature environment is 300-400°C.

[0038] In some preferred embodiments, the substrate comprises an aerospace vehicle or a nuclear power bearing, and the aerospace vehicle or nuclear power bearing comprises an engine, a turbine or a critical moving part.

[0039] In some preferred embodiments, the material of the substrate includes any one or more combinations of 304 steel, 316 steel, Ti6A14V, 9Cr18, and single crystal silicon wafer, but is not limited thereto.

[0040] In some preferred embodiments, the use is the use of the composite film with a multi-component multi-phase structure in the lubrication of the surface of an engine, a turbine or other key moving parts exposed to a high temperature environment during flight.

[0041] In some preferred embodiments, the thickness modulation ratio of the molybdenum disulfide layer to the tungsten diboride layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 3 to 5:1.

[0042] In some preferred embodiments, the molybdenum disulfide / tantalum / tungsten diboride composite layer includes 210 to 220 alternating stacked periodic layers, and each alternating stacked periodic layer contains a molybdenum disulfide layer and a tungsten diboride layer, the thickness of the molybdenum disulfide layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 6 to 7 nm (for example, 6 nm); the thickness of the tungsten diboride layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 2 to 3 nm (for example, 2 nm); the particle size of the tantalum nanoparticles is 0.5 to 1 nm.

[0043] In some preferred embodiments, the molybdenum disulfide in the molybdenum disulfide / tantalum / tungsten diboride composite layer grows along a (002) crystal plane parallel to the substrate.

[0044] In some preferred embodiments, the thickness of the titanium transition layer is 100-200 nm.

[0045] In some preferred embodiments, the thickness of the titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer is 200-300 nm.

[0046] In some preferred embodiments, the multi-component multi-phase structure layer has a thickness of 1.4-1.7 μm.

[0047] In some preferred embodiments, the composite film having a multi-component multi-phase structure has a thickness of 1.8 to 2.1 μm.

[0048] In some preferred embodiments, the surface roughness of the composite film is less than 4 nm.

[0049] In some preferred embodiments, the composite film has a hardness higher than 10.99 GPa under atmospheric conditions at 25° C., and a hardness / elasticity ratio greater than or equal to 0.094.

[0050] In some preferred embodiments, the composite film has a hardness higher than 6.15 GPa under atmospheric conditions at 100° C., and a hardness / elasticity ratio greater than or equal to 0.055.

[0051] In some preferred embodiments, the composite film has a hardness higher than 5.70 GPa under atmospheric conditions at 200° C., and a hardness / elasticity ratio greater than or equal to 0.055.

[0052] In some preferred embodiments, the composite film has a hardness higher than 4.40 GPa under 300° C. atmospheric conditions, and a hardness / elasticity ratio greater than or equal to 0.060.

[0053] In some preferred embodiments, the composite film has a hardness higher than 5.50 GPa under 400° C. atmospheric conditions, and a hardness / elasticity ratio greater than or equal to 0.084.

[0054] In some preferred embodiments, the friction coefficient of the composite film under 25°C atmospheric environment conditions is less than or equal to 0.093, and the wear rate is less than or equal to 2.23×10 -7 mm 3 / N·m.

[0055] In some preferred embodiments, the friction coefficient of the composite film under 100°C atmospheric environment conditions is less than or equal to 0.041, and the wear rate is less than or equal to 1.96×10 -7 mm 3 / N·m.

[0056] In some preferred embodiments, the composite film has a friction coefficient less than or equal to 0.036 and a wear rate less than or equal to 2.30×10 -7 mm 3 / N·m.

[0057] In some preferred embodiments, the composite film has a friction coefficient less than or equal to 0.060 and a wear rate less than or equal to 9.97×10 -7 mm 3 / N·m.

[0058] In some preferred embodiments, the composite film has a friction coefficient less than or equal to 0.093 and a wear rate less than or equal to 2.20×10 -6 mm 3 / N·m.

[0059] The composite film with a multi-element multi-phase structure in the present invention shows a higher hardness and hardness / elasticity ratio at a high temperature of 400°C than at 300°C. This improvement is attributed to the accelerated diffusion of tantalum atoms at high temperatures. Under the action of high-temperature heat energy, they migrate, so that the film has good thermal resistance. On the other hand, the diffusion of tantalum atoms fills the gaps in the crystal planes, making the structure of the film more compact, and its load-bearing capacity and hardness are further improved, and it shows a low friction coefficient and wear rate under high temperature conditions. Therefore, the molybdenum disulfide / tantalum / tungsten diboride nanocomposite multilayer film with a multi-element multi-phase structure can meet the requirements of stable lubrication and long-life reliable service of aerospace and nuclear power bearings under harsh and complex and variable working conditions. Engines, turbines and other key moving parts will be exposed to high temperature environments during flight, and need to provide long-lasting lubrication and anti-wear performance at 400°C, while high hardness improves its load-bearing capacity and durability.

[0060] In some preferred embodiments, the method for preparing the composite film having a multi-component multi-phase structure comprises:

[0061] By adopting unbalanced magnetron sputtering technology, a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-component multi-phase structure layer are sequentially deposited on the substrate surface, thereby obtaining a composite film with a multi-component multi-phase structure.

[0062] In some preferred embodiments, when preparing the composite film having a multi-component multi-phase structure, six-target technology is used for deposition, and two molybdenum disulfide targets, a titanium metal target, a molybdenum disulfide target, a tungsten diboride target and a tantalum target are arranged in a counterclockwise direction.

[0063] In some preferred embodiments, the method for preparing the composite film having a multi-component multi-phase structure specifically comprises:

[0064] The unbalanced magnetron sputtering technology is adopted, with titanium target as cathode target material, inert gas as working gas, target current applied to the titanium target, and negative bias applied to the substrate, so as to deposit a titanium transition layer on the substrate surface; wherein the target current of the titanium target is 3.0-5.0A, the substrate bias is -70--90V, the working gas flow rate is 12-16sccm, and the pressure of the reaction chamber is 1.0-4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 1200-1800s;

[0065] The invention adopts unbalanced magnetron sputtering technology, uses titanium target, molybdenum disulfide target, tungsten diboride target and tantalum target as cathode target materials, uses inert gas as working gas, applies target current to titanium target, molybdenum disulfide target, tungsten diboride target and tantalum target, and applies negative bias voltage to substrate, so as to deposit titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer on the surface of the titanium transition layer; wherein, the sputtering target current applied to the titanium target gradually decreases from 3.0 to 5.0A to 0, the sputtering target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6A, the sputtering target current applied to the tungsten diboride target gradually increases from 0 to 0.8A, the sputtering target current applied to the tantalum target gradually increases from 0 to 0.5A, the substrate bias voltage is -70 to -90V, the working gas flow rate is 12 to 16sccm, and the pressure of the reaction chamber is 1.0 to 4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 1200-1800s;

[0066] And, using unbalanced magnetron sputtering technology, using molybdenum disulfide target, tungsten diboride target, and tantalum target as cathode target materials, using inert gas as working gas, applying target current to the molybdenum disulfide target, tungsten diboride target, and tantalum target, and applying negative bias to the substrate, so as to deposit a multi-component multi-phase structure layer on the surface of the titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer; wherein the sputtering target current applied to the molybdenum disulfide target is 1.6A; the sputtering target current applied to the tungsten diboride target is 0.8A, the sputtering target current applied to the tantalum target is 0.5A, the substrate bias is -70 to -90V, the working gas flow rate is 12 to 16sccm, and the pressure of the reaction chamber is 1.0 to 4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 6000-8000s.

[0067] Further, the inert gas includes argon, but is not limited thereto.

[0068] Furthermore, the method for preparing the composite film with a multi-component multi-phase structure also includes: firstly installing the substrate on a metal biaxial rotating frame; wherein the rotation speed of the metal biaxial rotating frame is 2 rpm.

[0069] Furthermore, the method for preparing the composite film having a multi-element multi-phase structure further comprises: evacuating the reaction chamber to a vacuum degree of 3.0×10 -5 torr or less, and then the cleaned substrate is subjected to plasma etching; wherein the process conditions of the plasma etching treatment include: substrate bias voltage of -400 to -500 V, substrate temperature of 100 to 150° C., and etching time of 1200 to 1800 s.

[0070] In some preferred embodiments, the method for preparing the composite film having a multi-element multi-phase structure is to use an unbalanced magnetron sputtering technique, which specifically comprises the following steps:

[0071] (1) The titanium target current is 5.0 A, the substrate bias voltage is -70 to -90 V, the working gas is argon, the gas flow rate is 12 to 16 sccm, the deposition substrate temperature is 80 to 120 °C, and the pressure is 1.0 to 4.0 × 10 -3 torr, the deposition time is 1200-1800s, a titanium transition layer is deposited on the substrate surface, and the thickness of the titanium transition layer is controlled at 100-200nm;

[0072] (2) The titanium target current gradually decreased from 5.0 A to 0, the target current of the molybdenum disulfide target gradually increased to 1.6 A, the target current applied to the tungsten diboride target gradually increased to 0.8 A, and the target current applied to the tantalum target gradually increased to 0.5 A. The substrate bias voltage was -50 to -70 V, the working gas flow rate was 12 to 16 sccm, the substrate temperature was 80 to 120 °C, and the reaction chamber pressure was 1.0 to 4.0 × 10 -3 torr, the deposition time is 1200-1800s, and then a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer is deposited on the surface of the titanium transition layer, and the thickness of the titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer is controlled between 200 and 300nm;

[0073] (3) Maintaining the molybdenum disulfide target sputtering target current at 1.6A, the tungsten diboride target current at 0.8A, and the tantalum target current at 0.5A, until the deposition thickness of the molybdenum disulfide / tantalum / tungsten diboride composite layer reaches 1.4 to 1.7 μm; the total thickness of the composite film with a multi-component multi-phase structure reaches 1.8 to 2.1 μm.

[0074] In some embodiments, when the sputtering target current of the molybdenum disulfide target is 1.6A, the sputtering target current of the tungsten diboride target is 0.8A, and the tantalum target current is 0.5A, the thin film crystal structure preferentially grows as MoS2(002).

[0075] In some embodiments, the preparation method further comprises: controlling the rotation speed of the sample holder to be within 2 revolutions per minute, thereby obtaining a composite film having a multi-component multi-phase structure.

[0076] Furthermore, the preparation method further comprises: evacuating the reaction chamber to a predetermined vacuum degree (5×10 -5 torr or less), the substrate surface is subjected to plasma etching to remove the oxide on the substrate surface; the specific etching method includes applying a bias voltage of -400 to -500 V to the substrate, etching the substrate at a temperature of 100 to 150° C., and etching for 1200 to 1800 seconds.

[0077] Furthermore, the material of the substrate is not limited, and may be 304 steel, 316 steel, Ti6A14V, 9Cr18, single crystal silicon wafer, etc., but is not limited thereto.

[0078] The inventors of this case conducted the following performance tests on the composite film with a multi-component and multi-phase structure prepared above:

[0079] The hardness and elastic modulus of the film at room temperature and high temperature were measured using an MTS NanoIndenter G200 nanoindenter system equipped with a high-temperature heating device and a diamond Berkovich indenter. The indentation depth of the diamond indenter was less than 1 / 10 of the film thickness to minimize the influence of the substrate. The average value of the six points was finally measured. Measurement results: The hardness of the composite film at room temperature (25°C) was greater than 10.99GPa, and the hardness / elasticity ratio was greater than or equal to 0.094.

[0080] In the high-temperature nanoindentation test, the temperature was set at 100℃, 200℃, 300℃ and 400℃, the heating rate was 10℃ / min, the indentation depth was less than 1 / 10 of the film thickness, in order to avoid the influence of the substrate as much as possible, and the average value was finally measured at six points. The measurement results: at 100℃, the hardness of the composite film is higher than 10.99GPa, and the hardness / elasticity ratio is greater than or equal to 0.094; at 200℃, the hardness of the composite film is higher than 5.70GPa, and the hardness / elasticity ratio is greater than or equal to 0.055; at 300℃, the hardness of the composite film is higher than 4.40GPa, and the hardness / elasticity ratio is greater than or equal to 0.055; at 400℃, the hardness of the composite film is higher than 5.50GPa, and the hardness / elasticity ratio is greater than or equal to 0.084;

[0081] Atmospheric normal temperature and high temperature friction and wear tests, the high temperature friction and wear performance of the film was analyzed using Anton Paar's multifunctional high temperature friction tester, and the test temperatures were 100°C, 200°C, 300°C and 400°C. A GCr15 steel ball was used as the friction pair, and a cyclic rotation mode was adopted, with a linear speed of 9.42cm / s, a rotation radius of 3mm, a running time of 1h, and a normal load of 5N. A contact step profiler was used to measure the cross-section of the wear area, and the wear volume of the film was calculated by multiplying it by the sliding step length, and the wear rate was obtained by dividing the wear volume by the load and the total sliding distance.

[0082] Test results: The friction coefficient of the composite film provided by the present invention is less than or equal to 0.093 and the wear rate is less than or equal to 2.23×10 -7 mm 3 / N·m; friction coefficient at 100°C is less than or equal to 0.041, wear rate is less than or equal to 1.96×10 -7 mm 3 / N·m; friction coefficient is less than or equal to 0.036 at 200℃, wear rate is less than or equal to 2.30×10 - 7 mm 3 / N·m; friction coefficient at 300℃ is less than or equal to 0.060, wear rate is less than or equal to 9.97×10 -7 mm 3 / N·m; friction coefficient at 400℃ is less than or equal to 0.093, wear rate is less than or equal to 2.20×10 -6 mm 3 / N·m.

[0083] In summary, through the above technical scheme, the composite film provided by the present invention has excellent high-temperature mechanical properties and exhibits low friction and wear properties under high-temperature environments, which can meet the long-life and reliable service requirements of aerospace vehicles and nuclear power mechanical motion devices in harsh environments.

[0084] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0085] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0086] Example 1

[0087] In this embodiment, the base materials are 316 stainless steel and single crystal silicon wafer. Among them, the composite film with a multi-element multi-phase structure deposited with 316 stainless steel as the base material can be used for service performance testing, including related mechanical properties, atmospheric room temperature friction performance test and atmospheric high temperature friction performance test; the composite film with a multi-element multi-phase structure deposited with single crystal silicon wafer as the base material can be used for film thickness, surface roughness and structure tests. Using two different base materials, the steps and methods of film deposition are the same, and the difference in the base material itself has no effect on the physical and chemical properties of the film.

[0088] The unbalanced magnetron sputtering technology is used to prepare a composite film with a multi-component multi-phase structure on the substrate surface, which mainly includes the following steps:

[0089] The mechanically polished substrate was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; then placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use. The targets were arranged in a counterclockwise direction: two MoS2 targets (purity 99.9at.%), one Ti target (purity 99.9at.%), one MoS2 target (purity 99.9at.%), one WB2 target (purity 99.9at.%), and one Ta target (purity 99.99at.%). The cleaned substrate was placed in the chamber of the unbalanced magnetron sputtering system and evacuated to a vacuum degree of less than 5.0×10 -3 Pa, high-purity argon gas is filled into the chamber, and then the target is cleaned by sputtering with argon plasma for 30 minutes, and the substrate temperature is 100-120°C. Unbalanced magnetron sputtering technology is used, and the sample holder speed is set to 2 rpm to prepare and deposit MoS2 / Ta / WB2 composite films with multi-element and multi-phase structures. The specific steps are as follows:

[0090] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.

[0091] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 1.0 to 4.0 × 10 -3 torr, the deposition time was 1200s, and a Ti transition layer with a thickness of about 200nm was deposited on the substrate surface;

[0092] (3) Ti / MoS2 / Ta / WB2 gradient transition layer: The Ti target current is gradually reduced to 0 A, while the MoS2 target current is gradually increased to 1.6 A, the WB2 target current is increased to 0.8 A, and the Ta target current is increased to 0.5 A. The working gas is argon with a gas flow rate of 16 sccm. The substrate bias voltage is -50 V, the substrate deposition temperature is about 100 °C, and the pressure is about 1.0 to 4.0 × 10 -3 torr, the deposition time is 1800s, and a Ti / MoS2 / Ta / WB2 gradient transition layer is deposited on the surface of the Ti transition layer with a thickness of about 200nm;

[0093] (4) MoS2 / Ta / WB2 composite layer: The target current of MoS2, the target current of WB2, and the target current of Ta were kept at 1.6A, 0.8A, and 0.5A, and the other deposition parameters remained unchanged. The deposition time was 7000s. The thickness modulation ratio of the MoS2 layer and the WB2 layer was controlled to be 3:1. The thickness of the MoS2 layer was about 6nm, and the thickness of the WB2 layer was about 2nm. The particle size of the Ta nanoparticles was about 0.6nm. The thickness of the MoS2 / Ta / WB2 composite layer was about 1.4μm. The total thickness of the composite film with a multi-component multi-phase structure was controlled to be about 1.8μm.

[0094] The structure, morphology, mechanical properties and tribological properties of the composite film with multi-phase and multi-phase structure obtained by the above deposition are tested, including:

[0095] (1) Structural test:

[0096] The XRD results of the composite film with multi-phase structure are as follows: Figure 1 As shown, the film crystal structure has obvious preferential growth in the MoS2(002) orientation.

[0097] The cross-sectional TEM of the composite film is as follows Figure 2 As shown in the figure, the thickness of the Ti transition layer is about 200nm, the thickness of the Ti / MoS2 / Ta / WB2 gradient transition layer is about 200nm, and the thickness of the MoS2 / Ta / WB2 composite layer is about 1.4μm. The total thickness of the composite film is about 1.8μm. Furthermore, it can be seen from the figure that the layers are clearly separated, indicating that the construction of a composite film with a multi-element multi-phase structure can effectively improve the load-bearing capacity and mechanical properties of the film, and provide a structural basis for improving tribological properties and environmental adaptability.

[0098] High-resolution TEM of composite films Figure 3 As shown, in the MoS2 / Ta / WB2 composite layer, the thickness of the MoS2 layer is about 6nm, the thickness of the WB2 layer is about 2nm; the particle size of the Ta nanoparticles is about 0.6nm; the thickness modulation ratio of the MoS2 layer and the WB2 layer is 3:1, and Ta is distributed between the MoS2 layer and the WB2 layer as nanoparticles.

[0099] (2) Morphology test:

[0100] Composite cross-section SEM Figure 4a As shown, the thickness of the Ti transition layer is about 200nm, the thickness of the Ti / MoS2 / Ta / WB2 gradient transition layer is about 200nm, and the thickness of the MoS2 / Ta / WB2 composite layer is about 1.4μm. The total thickness of the composite film is about 1.8μm. Furthermore, the cross-sectional morphology of the film is dense.

[0101] The surface SEM images of the composite film are shown in Figure 5aAs shown, further, the surface of the film is flat.

[0102] The surface SPM image of the composite film is shown in Figure 6a As shown, further, the surface roughness of the film is about 3 nm.

[0103] (3) Mechanical properties test:

[0104] The hardness and elastic modulus of the film at room temperature and high temperature (25°C to 400°C) were measured using an MTS NanoIndenter G200 nanoindentation system. The indentation depth of the diamond indenter was 1 / 10 of the film thickness to avoid the influence of the matrix material. The average value was taken at six points. The test results are shown in Figure 2. Figure 7a and Figure 8 shown.

[0105] (4) Friction and wear performance test:

[0106] Anton Paar's multifunctional high-temperature friction tester was used to analyze the high-temperature tribological properties of the film. The test temperatures were 25°C, 100°C, 200°C, 300°C and 400°C. A GCr15 steel ball was used as the friction pair. The cyclic rotation mode was adopted. The linear speed was 9.42 cm / s, the rotation radius was 3 mm, the running time was 1 h, and the normal load was 5 N. The wear volume was measured using a contact step profiler. The wear volume was divided by the load and the total sliding distance to obtain the wear rate. The friction coefficient and wear rate of the composite film were tested in different atmospheric temperature environments. The results are as follows: Figure 10a-Figure 10e , Fig.11 , Fig.12 shown.

[0107] Comparative Example 1

[0108] In this comparative example, the base materials are 316 stainless steel and single crystal silicon wafer. Among them, the deposition of pure molybdenum disulfide film on 316 stainless steel as the base material can be used for service performance testing, including related mechanical properties, atmospheric room temperature and atmospheric high temperature friction performance tests, etc.; the deposition of pure molybdenum disulfide film on single crystal silicon wafer as the base material can be used for film thickness, surface roughness and structure testing.

[0109] The unbalanced magnetron sputtering technology is used to prepare pure molybdenum disulfide film on the substrate surface, which mainly includes the following steps:

[0110] The mechanically polished substrate was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; then placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use. The targets were arranged in a counterclockwise direction: two MoS2 targets (purity 99.9at.%), one Ti target (purity 99.9at.%), and three MoS2 targets (purity 99.9at.%). The cleaned substrate was placed in the chamber of the unbalanced magnetron sputtering system and evacuated to a vacuum degree of less than 5.0×10 -5 torr, high-purity argon gas was filled into the chamber, and then the target was cleaned by argon plasma sputtering for 30 minutes, and the substrate temperature was 100-120°C. Unbalanced magnetron sputtering technology was used, and the sample holder speed was set to 5 rpm to prepare and deposit pure MoS2 film. The specific steps are as follows:

[0111] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.

[0112] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 1.0 to 4.0 × 10 -3 torr, the deposition time was 1200s, and a Ti transition layer with a thickness of about 200nm was deposited on the substrate surface;

[0113] (3) Ti / MoS2 gradient transition layer: The Ti target current was gradually reduced to 0 A, while the MoS2 target current was gradually increased to 1.6 A. The working gas was argon with a gas flow rate of 16 sccm. The substrate bias voltage was -50 V, the substrate deposition temperature was about 100 °C, and the pressure was about 1.0 to 4.0 × 10 -3 torr, the deposition time is 1800s, and the thickness of the Ti / MoS2 gradient transition layer deposited on the surface of the Ti transition layer is about 200nm;

[0114] (4) Pure MoS2 film: The MoS2 target current was maintained at 1.6 A and the deposition time was 7000 s; the total thickness of the pure MoS2 film was approximately 2.7 μm.

[0115] The structure, morphology, mechanical properties and tribological properties of the pure MoS2 film obtained by the above deposition were tested, including:

[0116] (1) Structural test:

[0117] The XRD results of the pure MoS2 film are as follows Figure 1 As shown, the diffraction peak intensity of the MoS2 (002) crystal plane of pure MoS2 film is obviously lower.

[0118] (2) Morphology test:

[0119] The cross-sectional SEM of the film is as follows Figure 4b As shown, the thickness of the Ti transition layer is about 200nm, the thickness of the Ti / MoS2 gradient transition layer is about 200nm, and the thickness of MoS2 is about 2.3μm. The total thickness of the pure MoS2 film is about 2.7μm. Furthermore, the cross-sectional morphology of the film is loose and exhibits typical columnar crystals.

[0120] The surface SEM image of the film is as follows Figure 5b As shown, further, the surface morphology of the film is not smooth.

[0121] The surface SPM image of the film is shown in Figure 6b As shown, the surface roughness of the film is about 14 nm.

[0122] (3) Mechanical properties test:

[0123] The MTS NanoIndenter G200 nanoindentation system was used to measure the hardness and elastic modulus of the film at room temperature and high temperature (25°C to 300°C). The penetration depth of the diamond indenter was 1 / 10 of the film thickness to avoid the influence of the matrix material. The average value was taken at six points. The test results are shown in the figure. Figure 7b and Figure 8 shown.

[0124] (4) Friction and wear performance test:

[0125] Anton Paar's multifunctional high-temperature friction tester was used to analyze the high-temperature tribological properties of the film. The test temperatures were 25°C, 100°C, 200°C and 300°C. A GCrl5 steel ball was used as the friction pair. The cyclic rotation mode was adopted. The linear speed was 9.42 cm / s, the rotation radius was 3 mm, the running time was 1 h, and the normal load was 5 N. The wear volume was measured using a contact step profiler. The wear volume was divided by the load and the total sliding distance to obtain the wear rate. The friction coefficient and wear rate of the film were tested in different atmospheric temperature environments. Figure 10a-Figure 10d , Fig.11 , Fig.12 shown.

[0126] Comparative Example 2

[0127] In this comparative example, the base materials are 316 stainless steel and single crystal silicon wafer. Among them, the deposition of molybdenum disulfide / tungsten diboride film using 316 stainless steel as the base material can be used for service performance testing, including related mechanical properties, atmospheric room temperature and atmospheric high temperature friction performance tests, etc.; the deposition of molybdenum disulfide / tungsten diboride film using single crystal silicon wafer as the base material can be used for film thickness, surface roughness and structure testing.

[0128] The unbalanced magnetron sputtering technology is used to prepare the molybdenum disulfide / tungsten diboride film on the substrate surface, which mainly includes the following steps:

[0129] The mechanically polished substrate was placed in an acetone solution for ultrasonic cleaning for 30 minutes and dried with nitrogen; then placed in an anhydrous ethanol solution for ultrasonic cleaning for 20 minutes and dried with nitrogen for later use. The targets were arranged in a counterclockwise direction: two MoS2 targets (purity 99.9at.%), one Ti target (purity 99.9at.%), two MoS2 targets (purity 99.9at.%), and one WB2 target (purity 99.9at.%). The cleaned substrate was placed in the chamber of the unbalanced magnetron sputtering system and evacuated to a vacuum degree of less than 5.0×10 -3 Pa, high-purity argon gas is filled into the chamber, and then the target is cleaned by argon plasma sputtering for 30 minutes, and the substrate temperature is 100-120°C. Unbalanced magnetron sputtering technology is used, and the sample holder speed is set to 2 rpm to prepare and deposit MoS2 / WB2 thin films. The specific steps are as follows:

[0130] (1) Substrate surface treatment: A bias voltage of -500 V was applied to the substrate, and plasma etching was performed for 30 min at a substrate temperature of approximately 100°C to remove oxides on the substrate surface.

[0131] (2) Ti transition layer deposition: Ti target current is 5.0 A, substrate bias voltage is -70 V, working gas is argon, gas flow rate is 16 sccm, substrate deposition temperature is 80 °C, pressure is about 1.0 to 4.0 × 10 -3 torr, the deposition time was 1200s, and a Ti transition layer with a thickness of about 200nm was deposited on the substrate surface;

[0132] (3) Ti / MoS2 / WB2 gradient transition layer: The Ti target current is gradually reduced to 0 A, while the MoS2 target current is gradually increased to 1.6 A and the WB2 target current is gradually increased to 0.8 A. The working gas is argon with a gas flow rate of 16 sccm. The substrate bias voltage is -50 V, the substrate deposition temperature is about 100 °C, and the pressure is about 1.0 to 4.0 × 10 -3 torr, the deposition time is 1800s, and a Ti / MoS2 / WB2 gradient transition layer is deposited on the surface of the Ti transition layer with a thickness of about 200nm;

[0133] (4) MoS2 / WB2 composite layer: The MoS2 target current was kept at 1.6 A, the WB2 target current was kept at 0.8 A, the other deposition parameters remained unchanged, and the deposition time was 7000 s; the thickness modulation ratio of the MoS2 layer and the WB2 layer was controlled to be 3-5; the thickness of the MoS2 layer was about 6 nm, and the thickness of the WB2 layer was about 2 nm; the thickness of the MoS2 / WB2 composite layer was about 1.9 μm; and the total thickness of the film was about 2.3 μm.

[0134] The structure, morphology, mechanical properties and tribological properties of the MoS2 / WB2 film obtained by the above deposition were tested, including:

[0135] (1) Structural test:

[0136] The XRD results of the MoS2 / WB2 film are as follows Figure 1 As shown, the film crystal structure has obvious preferential growth in the MoS2(002) orientation.

[0137] (2) Morphology test:

[0138] The cross-sectional SEM images of the films are shown in Figure 2. Figure 4c As shown, the thickness of the Ti transition layer is about 200nm, the thickness of the Ti / MoS2 / WB2 gradient transition layer is about 200nm, and the thickness of the MoS2 / WB2 composite layer is about 1.9μm. The total thickness of the film is about 2.3μm. Furthermore, the cross-sectional morphology of the film is dense.

[0139] The surface SEM image of the film is as follows Figure 5c As shown, further, the surface morphology of the film is not smooth.

[0140] The surface SPM image of the film is shown in Figure 6c As shown, the surface roughness of the film is about 6 nm.

[0141] (3) Mechanical properties test:

[0142] The MTS NanoIndenter G200 nanoindentation system was used to measure the hardness and elastic modulus of the film at room temperature and high temperature (25°C to 400°C). The penetration depth of the diamond indenter was 1 / 10 of the film thickness to avoid the influence of the matrix material. The average value was taken after measuring six points. The test results are shown in the figure. Figure 7c and Figure 8 shown.

[0143] (4) Friction and wear performance test:

[0144] Anton Paar's multifunctional high-temperature friction tester was used to analyze the high-temperature tribological properties of the film. The test temperatures were 25°C, 100°C, 200°C, 300°C and 400°C. A GCr15 steel ball was used as the friction pair. The cyclic rotation mode was adopted. The linear speed was 9.42 cm / s, the rotation radius was 3 mm, the running time was 1 h, and the normal load was 5 N. The wear volume was measured using a contact step profiler. The wear volume was divided by the load and the total sliding distance to obtain the wear rate. The friction coefficient and wear rate of the film were tested in different atmospheric temperature environments. Figure 10a-Figure 10e , Fig.11 , Fig.12 shown.

[0145] The properties of the films prepared in Example 1 and Comparative Examples 1-2 at 300°C and 400°C are shown in Table 1.

[0146] Table 1

[0147]

[0148]

[0149] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0150] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. Use of a composite film with a multi-component multi-phase structure in lubrication of aerospace or nuclear power bearing surfaces under high temperature conditions, characterized in that: The composite film includes a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-phase structure layer which are sequentially formed on the surface of a substrate; wherein the multi-phase structure layer includes a molybdenum disulfide / tantalum / tungsten diboride composite layer, the molybdenum disulfide / tantalum / tungsten diboride composite layer includes tantalum nanoparticles, a molybdenum disulfide layer and a tungsten diboride layer, and the tantalum nanoparticles are distributed between the molybdenum disulfide layer and the tungsten diboride layer.

2. The use according to claim 1, characterized in that: The temperature of the high temperature environment is 300-400°C; And / or, the substrate includes an aerospace vehicle or a nuclear power bearing, and the aerospace vehicle or nuclear power bearing includes an engine, a turbine or a key moving part; and / or, the material of the substrate includes any one or more combinations of 304 steel, 316 steel, Ti6A14V, 9Cr18, and a single crystal silicon wafer; And / or, the use is the use of the composite film with a multi-component and multi-phase structure in the lubrication of the surface of an engine, a turbine or other key moving parts exposed to a high temperature environment during flight.

3. The use according to claim 1, characterized in that: The thickness modulation ratio of the molybdenum disulfide layer to the tungsten diboride layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 3N5:1; And / or, the molybdenum disulfide / tantalum / tungsten diboride composite layer includes 210 to 220 alternating stacked periodic layers, and each alternating stacked periodic layer contains a molybdenum disulfide layer and a tungsten diboride layer, the thickness of the molybdenum disulfide layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 6N7nm; the thickness of the tungsten diboride layer in the molybdenum disulfide / tantalum / tungsten diboride composite layer is 2 to 3nm; the particle size of the tantalum nanoparticles is 0.5 to 1nm. And / or, the molybdenum disulfide in the molybdenum disulfide / tantalum / tungsten diboride composite layer grows along a (002) crystal plane parallel to the substrate.

4. The use according to claim 1, characterized in that: The thickness of the titanium transition layer is 100 to 200 nm; And / or, the thickness of the titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer is 200-300 nm; And / or, the thickness of the multi-component multi-phase structure layer is 1.4-1.7 μm; And / or, the composite film having a multi-component multi-phase structure has a thickness of 1.8 to 2.1 μm.

5. The use according to claim 1, characterized in that: The surface roughness of the composite film is less than 4 nm; and / or, the composite film has a hardness higher than 10.99 GPa under atmospheric conditions of 25° C., and a hardness / elasticity ratio greater than or equal to 0.094; and / or, the composite film has a hardness of higher than 6.15 GPa under atmospheric conditions at 100° C., and a hardness / elasticity ratio greater than or equal to 0.055; and / or, the composite film has a hardness of higher than 5.70 GPa under atmospheric conditions at 200° C., and a hardness / elasticity ratio greater than or equal to 0.055; and / or, the composite film has a hardness of higher than 4.40 GPa under 300° C. atmospheric conditions, and a hardness / elasticity ratio greater than or equal to 0.060; and / or, the composite film has a hardness of higher than 5.50 GPa under atmospheric conditions at 400° C., and a hardness / elasticity ratio greater than or equal to 0.084; And / or, the friction coefficient of the composite film under 25°C atmospheric environment conditions is less than or equal to 0.093, and the wear rate is less than or equal to 2.23×10 -7 mm 3 / N·m; And / or, the friction coefficient of the composite film under 100°C atmospheric environment conditions is less than or equal to 0.041, and the wear rate is less than or equal to 1.96×10 -7 mm 3 / N·m; And / or, the composite film has a friction coefficient less than or equal to 0.036 and a wear rate less than or equal to 2.30×10 -7 mm 3 / N·m; And / or, the composite film has a friction coefficient less than or equal to 0.060 and a wear rate less than or equal to 9.97×10 -7 mm 3 / N·m; And / or, the composite film has a friction coefficient less than or equal to 0.093 and a wear rate less than or equal to 2.20×10 -6 mm 3 / N·m.

6. The use according to claim 1, characterized in that: The method for preparing the composite film having a multi-component multi-phase structure comprises: By adopting unbalanced magnetron sputtering technology, a titanium transition layer, a titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer and a multi-component multi-phase structure layer are sequentially deposited on the substrate surface, thereby obtaining a composite film with a multi-component multi-phase structure.

7. The use according to claim 6, characterized in that: When preparing the composite film with a multi-element multi-phase structure, six-target technology is used for deposition, and two molybdenum disulfide targets, a titanium metal target, a molybdenum disulfide target, a tungsten diboride target and a tantalum target are arranged in sequence in a counterclockwise direction.

8. The use according to claim 6, characterized in that The method for preparing the composite film having a multi-component multi-phase structure specifically comprises: The unbalanced magnetron sputtering technology is adopted, with titanium target as cathode target material, inert gas as working gas, target current applied to the titanium target, and negative bias applied to the substrate, so as to deposit a titanium transition layer on the substrate surface; wherein the target current of the titanium target is 3.0-5.0A, the substrate bias is -70--90V, the working gas flow rate is 12-16sccm, and the pressure of the reaction chamber is 1.0-4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 1200-1800s; The invention adopts unbalanced magnetron sputtering technology, uses titanium target, molybdenum disulfide target, tungsten diboride target and tantalum target as cathode target materials, uses inert gas as working gas, applies target current to titanium target, molybdenum disulfide target, tungsten diboride target and tantalum target, and applies negative bias voltage to substrate, so as to deposit titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer on the surface of the titanium transition layer; wherein, the sputtering target current applied to the titanium target gradually decreases from 3.0 to 5.0A to 0, the sputtering target current applied to the molybdenum disulfide target gradually increases from 0 to 1.6A, the sputtering target current applied to the tungsten diboride target gradually increases from 0 to 0.8A, the sputtering target current applied to the tantalum target gradually increases from 0 to 0.5A, the substrate bias voltage is -70 to -90V, the working gas flow rate is 12 to 16sccm, and the pressure of the reaction chamber is 1.0 to 4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 1200-1800s; And, using unbalanced magnetron sputtering technology, using molybdenum disulfide target, tungsten diboride target, and tantalum target as cathode target materials, using inert gas as working gas, applying target current to the molybdenum disulfide target, tungsten diboride target, and tantalum target, and applying negative bias to the substrate, so as to deposit a multi-component multi-phase structure layer on the surface of the titanium / molybdenum disulfide / tantalum / tungsten diboride gradient transition layer; wherein the sputtering target current applied to the molybdenum disulfide target is 1.6A; the sputtering target current applied to the tungsten diboride target is 0.8A, the sputtering target current applied to the tantalum target is 0.5A, the substrate bias is -70 to -90V, the working gas flow rate is 12 to 16sccm, and the pressure of the reaction chamber is 1.0 to 4.0×10 -3 torr, substrate temperature is 80-120°C, and deposition time is 6000-8000s.

9. The use according to claim 8, characterized in that The method for preparing the composite film with a multi-component multi-phase structure further includes: firstly installing the substrate on a metal biaxial rotating frame; wherein the rotation speed of the metal biaxial rotating frame is 2 rpm.

10. The use according to claim 8, characterized in that The method for preparing a composite film having a multi-component multi-phase structure further comprises: evacuating the reaction chamber to a vacuum degree of 3.0×10 -5 torr or less, and then the cleaned substrate is subjected to plasma etching; wherein the process conditions of the plasma etching treatment include: substrate bias voltage of -400 to -500 V, substrate temperature of 100 to 150° C., and etching time of 1200 to 1800 s.

Citation Information

Cited By

  • Molybdenum disulfide composite film and preparation method and application thereof

    CN121518995A